(untitled) (Andamios, Revista de Investigación Social, 2007)
Party struggles constitute an important moment to analyze the interaction between the political and the media systems. Press representations by means of production and treatment of information are key aspects for the constitution of the thematic agenda. The internal selection of the candidate to the government of the State of Mexico by PRI for the 2005 elections is an example of the construction of political discourse through journalistic practices. This relationship uncovers newspapers as subordinates to political power. The degree of subordination of the press is analyzed in three newspapers where the results highlight a press that supports official versions of the internal process that simulate competition and division of the local PRI.